Trajectory planning and simulation for 3d printing process - Ng, Chin Yong (2022)
The demand for Fused Deposition Modelling (FDM) 3D printing technology is skyrocketing among hobbyist makers in recent years especially during the outbreak of pandemic Covid 19. 3D printing community has increased drastically with engagement of hobbyists and users from non-engineering background. The main concern from non-engineering users are affordability, operability, and efficiency. Affordability refers to the financial burden upon purchasing large amount of printing material for reprint the printouts that are not satisfactory. Operability refers to the knowledge needed to adjust the printer's settings. Efficiency refers to the amount of time spent printing on printouts that are not satisfactory. With these feedbacks from the users, a stimulator called CY simulator is proposed in this project to resolve the nonengineering users' concerns. The aim of this project is to develop a FDM 3D printer simulator that can generate the surface and infill of a 3D print from a STL file. 3D printing process will be simulated according to the generated vertices and printing time will be estimated. Development of the simulator was started with the development of STL file reader to extract the triangular facets’ vertices from a STL file in ASCII format. The extracted vertices will be used as the input of slicer to slice the model into layers with user-defined layer height. The slicing method used is basic slicing. The slicing algorithm consists of two sections: intersection point tracking algorithm and contour creation algorithm. The output of slicing algorithm will be used as input of infill generator to generate infill vertices based on the infill density and infill pattern that decided by users. Next, the output of slicer and infill generator will be rendered accordingly to simulate a lifelike 3D printing process. Vertices are connected by using a hollow cylinder to represent the 3D printing material. Moreover, printing time is estimated by dividing the distance between each vertex by the default printing speed. After that, several experiments were conducted to examine the feasibility of the simulator in terms of layer height, infill density, top and bottom thickness, and estimated printing time. According to the result, the layer height, infill and top/bottom thickness generated by the simulator can achieve 100 % similarity with the actual print. Apart from that, the simulator has 100 % accuracy of estimating printing time for objects that have lesser layers. However, less accurate of estimating printing time for models that have many layers. This is because the travelling time for the nozzle to travel from the last position of the layer to the first position of the next layer is not taken into consideration of the printing time. The effect of travelling time on the estimated printing time increases with the number of layers and the distance of the travelling time from last point of a layer to the next layer.